Digital rolling role across global classrooms: a geodramatic framework. Issue 1 (2nd January 2016) - Hatton, Christine; Mooney, Mary; Nicholls, Jennifer
Abstract: This article focuses on the Sydney case study within the 2013 international Water Reckoning Project (www.water-reckoning.net ) – a project which repurposed Dorothy Heathcote's rolling role curriculum model with digital technologies to connect students and teachers around the world in a common drama, considering the 'what if' context of a fictional community, called 'Ardus Unda', which was on the brink of an imagined environmental disaster. The article proposes a new geodramatic inquiry framework that draws upon place pedagogy and social ecology to examine the positioning of learners as the drama opened up new ways for them to consider their collective and personal responses to local and global environmental issues. In this project experiences were curated by teacher/researchers and student's dramatic content was uploaded online for a range of audiences. In analysing the role-based exchanges between students and teachers, as well as focus group data, the writers offer a new framework for researching drama. This geodramatic analysis examines the dynamic interplay of place, time and relationships within a digital rolling role project. Researchers of the Sydney case study also consider the tensions and possibilities of situatedness in a global drama and the implications for applying this digital pedagogical model.